Діяльність альтернативних суспідьно - політичних рухів : виклики та можливості для демократії - Ігнатов, П.С.; Игнатов, П.С.; Ignatov, P (My University, 2012)
The article investigates the actual topic – of new social and political movements that create new challenges for democratic institutions. Meanwhile, environmental, alternative and feminist movements contribute to the growth of political activity of citizens, increasing their awareness, opening the possibility for democratic development.
Ігнатов П.С. Діяльність альтернативних суспідьно - політичних рухів : виклики та можливості для демократії / П.С.Ігнатов // Актуальні проблеми політики : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), М. А. Польовий (відп. секр.) [та ін.] ; НУ «ОЮА», Південноукр. центр гендер. проблем. – Одеса, 2012. – Вип. 47. – С. 36 - 41.
Keywords: Альтернативні суспільно - політичні рухи; Діяльність суспільно - політичних рухів; Демократичний розвиток; Демократическое развитие; Деятельность общественно - политических движений; Альтернативные общественно - политические движения; Alternative socio - political movements; Activities socio - political movements; Democratic Development